BOILED CHICKEN EGGS AGAINST RATE OF PERINEUM TEARS ON POSTPARTUM MOTHERS IN KRAMAT HEALTH CENTER, TEGAL REGENCY - Nurhayati Nurhayati; Iroma Maulida; Adevia Maulidya Chikmah (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
Injuries after childbirth are one of the causes of labour infections among other causes. Factors that can accelerate wound healing include nutrition. Nutrition plays a role in helping the process of metabolism, maintenance and formation of new tissue. Egg whites contain more nutrients than egg yolks which can heal perineal suture wounds in mothers after childbirth. The study population was postpartum mothers with perineal suture wounds at Kramat Public Health Center on January 7-February 2, 2019. This study used a quasi-experimental design with the Pretest and Posttest With Control Group Design approach, where respondents divided into intervention groups and control groups of 20 respondents. The wound degree observed at the beginning of the observation and the rate of wound healing at the end. In the intervention group, the respondent required to eat five egg whites for six days. Data analysis was performed with ANOVA test (α: 5%; 95% Confident Interval) to see the effect of consumption patterns of chicken egg white with the level of wound healing perineum. The results showed an influence of consumption patterns of boiled chicken egg white on the rate of perineal suture wounds healing as indicated by the higher number of respondents with a reasonable wound healing rate in the intervention group of 62.5% (5 people) compared to the control group, which was 42.9% (3 people) and from the Anova test results obtained a p-value of 0.015. Thus it is recommended that postpartum mothers consume many egg whites in order to accelerate the healing of perineal wounds to prevent infections due to perineal wounds. Keywords: Egg white, Perineal suture wounds Healing